Relation between climate and vegetation along a Mediterranean-Temperate boundary in central Italy - Blasi, C; Carranza, M L; Filesi, L; Tilia, A; Acosta, A (Global Ecology and Biogeography, 1999)
The relationship between climate and vegetation was investigated along a Mediterranean-Temperate boundary in central Italy. The study area is a transition zone between the Temperate (Eurosiberian) and Mediterranean regions and has an altitudinal range of almost 1750 m. Ordination and cluster analysis were used. The results did not show any sharp boundary but a climate-vegetation mosaic ranging from upper mountain thermotype and lower hyperhumid ombrotype with Fagus sylvatica L. woodlands at higher altitudes, to meso-Mediterranean thermotype and lower subhumid ombrotype with Mediterranean maquis and Quercus ilex L. woods on the coast. Six phytoclimatic groups are distinguished and described in terms of climatic parameters, vegetation types and morphological and chorological traits. These parameters indicate a change without sharp discontinuities between groups. The Mediterranean to Temperate transition in this Tyrrhenian sector is broad and includes most of the study area.
Keywords: bioclimatology; climatic indices; Mediterranean vegetation; phytoclimatic groups; temperate woodlands; transition areas

Climatic classification and ordination of the Spanish Sistema Central: relationships with potential vegetation - Gavilán, R G; Fernández-González, F; Blasi, C (Plant Ecology, 1998)
Monthly precipitation and monthly mean temperature records from 255 meteorological stations in Central Spain (Spanish Sistema Central) were analyzed by cluster and principal component analyses. Classiﬁcation separated 14 groups according to altitude, geographical distribution, as well as the combination of rainfall and temperature. The ﬁrst cluster emerged as signiﬁcantly higher and colder than the second. Then, two ordinations were carried out: one for the 14 groups extracted from the classiﬁcation and a second for the total station pool. The second ordination was compared with potential natural vegetation data taken around each station. The ﬁrst ordination summarized the principal climatic characteristics of the Spanish Sistema Central: its behaviour is that of a typical Mediterranean mountainous territory combining summer aridity and variation of temperature with altitude and the inﬂuence of winter winds. The ordination of all stations reﬂected a thermal, rainfall and summer aridity gradient. Meteorological stations situated at the highest altitude or with highest precipitation records characterized by scrub communities or pine woods and Quercus pyrenaica forests, appeared well-separated along the ﬁrst two axes. Only the most thermophilous Q. rotundifolia associations could be clearly separated. The fourth axis was useful in clarifying some vegetation overlap of deciduous and sclerophyllous forests, along an east-west summer aridity gradient.
Keywords: climate; cluster analysis; potential vegetation; Precipitation; Principal component analysis; Spain; Temperature

Life forms variability of mediterranean sclerophyllous forests - Blasi, C; Mazzoleni, S; Spada, F; Stanisci, A (Plant Ecology, 1990)
Variations in Raunkiaer's life-forms spectra for mature Quercus ilex forest stands in N-Mediterranean basin were examined in order to assess their predictability in local vegetation analysis. Physiognomic variations in Quercus ilex communities appear to be mainly determined by structural variations due to intrinsic characteristics (long-term human disturbance all over their range) and to different dynamical status of the stands, without any geographical pattern.
Keywords: Mediterranean basin; raunkiaer's life-forms; sclerophyllous forests